2007
DOI: 10.1002/ejic.200700549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deprotonation of a Benzimidazolyl Ligand on the Redox Potential and the Structures of Mononuclear Ruthenium(II) Complexes

Abstract: A monoruthenium(II) complex of the benzimidazolyl ligand and its deprotonated counterpart were prepared and structurally characterized. The reversible protonation/deprotonation process of the ancillary ligand switches the redox po-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The above experiments indicate that H 3 TMA is necessary for the redox reaction. We know that the distal deprotonation of imidazole can reduce the redox potential of metal center. The more deprotonation of H 2 biim ligands makes the redox potentials of Ru(II) complex shift to a less positive value. Crystal structure of 1 shows that there are 6-fold robust hydrogen bonded interactions between one [Ru(H 2 biim) 3 ] 3+ cation and three TMA anions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The above experiments indicate that H 3 TMA is necessary for the redox reaction. We know that the distal deprotonation of imidazole can reduce the redox potential of metal center. The more deprotonation of H 2 biim ligands makes the redox potentials of Ru(II) complex shift to a less positive value. Crystal structure of 1 shows that there are 6-fold robust hydrogen bonded interactions between one [Ru(H 2 biim) 3 ] 3+ cation and three TMA anions.…”
Section: Resultsmentioning
confidence: 99%
“…2 Furthermore, the imidazole-like ligand was widely used as one of the proton carriers because the distal deprotonation of the ligand bearing the imidazole-like component reduces the redox potential of metal center. [13][14][15][16][17] Recently, the strategy of second-sphere coordination has been employed to design ionic receptors based on 2,2 0 -biimidazole (H 2 biim) and 2,2 0 -bibenzimidazole (H 2 bbim) complexes. [18][19][20][21] The most important feature for such a complex is that the chelating coordination enforces the syn conformation, then engages in robust hydrogen bonding via the externally directed pair of N-H groups of the H 2 biim and H 2 bbim ligands to the carboxylate group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We know that the distal deprotonation of imidazole can reduce the redox potential of metal center. [23][24][25][26] Our previous study showed that the addition 1 equiv of acetate to the solution of [Ru(bpy) 2 (H 2biim)] 2+ shifted the absorption band from 485 nm to 507 nm due to the monodeprotonation of the H 2 biim ligand. 27 In this case, each [Ru(H 2 biim) 3 ] 2+ cation can form 6-fold robust hydrogen bonds with three acetate anions, inducing deprotonation at three sites.…”
Section: Solid-state Synthesis Ofmentioning
confidence: 99%
“…22 It was proved that the increased deprotonation at remote sites of imidazole ligands resulted in a shift in the redox potentials of a metal center to much less positive values. [23][24][25][26] This may afford an effective approach for the preparation of high status metal complexes via modification of the potential. On the other hand, the complex {[Ru(H 2 biim) 3 ](TMA)}$DMF$9H 2 O (H 3 TMA ¼ trimesic acid) which has a three dimensional network was obtained serendipitously during the complexation of [Ru(H 2 biim) 3 ](PF 6 ) 2 and H 3 TMA in a solution of DMF-EtOH at room temperature.…”
Section: Introductionmentioning
confidence: 99%